Plant in vitro cultures: A promising and emerging technology for the feasible production of antidiabetic metabolites in Caralluma tuberculata - Ali, Amir; Mashwani, Zia-ur-Rehman; Ahmad, Ilyas; Raja, Naveed Iqbal; Mohammad, Sher; Khan, Safir Ullah (Frontiers in Endocrinology, 2022)
Caralluma tuberculata, a medicinal and edible plant of the genus Caralluma, belongs to the family Asclepiadaceae. Traditionally, its succulent stems are used as folk medicine for life-threatening diabetes mellitus (DM) disease. Its antidiabetic potential is ascribed to the presence of various secondary metabolites (e.g., pregnane glycosides, flavone glycosides, megastigmane glycosides, polyphenols, ferulic acid, quercetin, and bitter principles, among others) that act as effective and safe antidiabetic agents. The mechanisms of these bioactive secondary metabolites in C. tuberculata herbal medicine include lowering the blood glucose level, stimulating B cells of the pancreas to release more insulin, enhancing the sensitivity of the insulin receptor, inhibiting the action of glucagon and the hydrolysis of glycogen, and increasing the use of glucose in tissues and organ. However, overexploitation, alterations in natural environmental conditions, lower seed viability, and slow growth rate are responsible for the extinction of species from natural habitats, then becoming critically endangered species according to the International Union for Conservation of Nature Red List categories. Therefore, its limited availability does not meet the higher worldwide market demand of C. tuberculata as an antidiabetic drug. Thus, for its conservation and sustainable utilization, researchers across the globe are working on devising strategies to conserve and improve biomass along with the secondary metabolite profiles of C. tuberculata using in vitro approaches. The current review describes the recent progress on antidiabetic phytoconstituents, their cellular mechanisms, and their subsequent clinical outcomes in the drug discovery management of DM. Moreover, in vitro methods such as callus culture, micropropagation, and nano-elicitation strategies for conserving and producing bioactive secondary metabolites have been concisely reviewed and discussed.